How Changes in Psychosocial Job Characteristics Impact Burnout in Nurses: A Longitudinal Analysis - Pisanti, Renato; van der Doef, Margot; Maes, Stan; Meier, Laurenz Linus; Lazzari, David; Violani, Cristiano (Frontiers in Psychology, 2016)
The main aim of this longitudinal study was to test the Job Demand-Control-Support (JDCS) model and to analyze whether changes in psychosocial job characteristics are related to (changes in) burnout. Previous studies on the effects of JDCS variables on burnout dimensions have indicated that the iso strain hypothesis (i.e., high job demands, low control and low support additively predict high stress reactions) and the buffer hypotheses (i.e., high job control and/or social support is expected to moderate the negative impact of high demands on stress reactions) have hardly been examined concurrently in a longitudinal design; and that the effects of changes of psychosocial job variables on burnout dimensions have hardly been analysed. This two wave study was carried out over a period of 14 months in a sample of 217 Italian nurses. Method: Hierarchical regression analyses were used to test the cross lagged main and interactive effects of JDCS variables, and to analyse the across-time effects of changes in JDCS dimensions on burnout variables. The Time 1 job characteristics explained 2 to 8% of the variance in the Time 2 burnout dimensions, but no support for the additive or the buffer hypothesis of the JDCS model was found. Changes in job characteristics explained an additional 3 to 20% of variance in the Time 2 burnout dimensions. Specifically, high levels of emotional exhaustion at Time 2 were explained by high levels of social support at Time 1, and unfavourable changes in demands, control and support over time; high depersonalisation at Time 2 was explained by high social support at time 1 and by an increase in demands over time; and high personal accomplishment at Time 2 was predicted by high demands, high control, interactive effect demands X control X social support, at Time 1, and by a decrease in demands over time. No reversed effects of burnout on work characteristics have been found. Our findings suggest that the work environment is subject to changes: the majority of employees experienced considerable changes in all job conditions over time. These changes impacted employee burnout. Limitations and implications of the study are discussed.